Demand-Supply Gap Analysis And Fleet Adjusment Strategy For Public Transport In Bekasi (Study Case K-19a) - Tatang Adhiatma; R. Caesario Boing, R,R.; Torang Hutabarat; Adithya Prayoga S; Aan Sunandar; Gilbert Matthew (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2025)
Bekasi City as one of the main buffers of DKI Jakarta is experiencing rapid population growth, accompanied by an increasing need for public transportation. Urban Transportation (Angkot) K19A is one of the vital modes of transportation for the community, especially for trips to work, school, and shopping centers. However, the increasing number of users means that the K19A fleet is often unable to meet the needs of the community, which is characterized by passenger density during peak hours and long waiting times. This condition has the potential to reduce the quality of service and encourage a shift to private vehicles, which can worsen congestion and air pollution. This study aims to analyze the need for additional K19A fleets based on passenger demand data, travel patterns, and route efficiency. By using a data-based approach, the results of the study are expected to be the basis for policy makers in formulating strategies to improve more effective and sustainable public transportation services in Bekasi City